Development of a visible spectrophotometric method for the assay of Methyldopa following oxidative coupling with N-(1-naphthyl) ethylenediamine dihydrochloride (2015)
Background: Methyldopa is a centrally acting hypertensive drug that remains one of the choice treatment options in the management of hypertension in pregnancy and during surgical anaesthesia. Although a number of methods of analysis are available, most employ sophisticated techniques and strict experimental conditions. Objective: To develop and validate a simple visible spectrophotometric analysis for the quantitative determination of methyldopa in bulk and dosage forms. Method: The method was based on the oxidative coupling reaction between methyldopa and N-(1-naphthyl) ethylenediamine (Bratton-Marshall’s reagent) to generate a blue chromogen. Reactions variables critical to optimal response were established. Various analytical and validation parameters including repeatability, reproducibility and selectivity were also determined. Results: The calibration graph was linear between 30 and 80 μg/ml at 580 nm with a correlation coefficient of 0.9996. The apparent molar absorptivity was 1.52 ×103 L mol−1 cm−1 while the limits of detection and quantification were 9.3 and 31 μg/ml respectively. The method was accurate and precise with recovery in the range of 99.26-101.30 % and intra- and inter-day precision (%RSD) at three different concentrations less than 1.0%. When applied to the analysis of dosage form, there was no statistical difference between the new method and the official method. There was no interference from commonly used excipients. Conclusion: The method is rapid, simple and cost-effective. It can serve as a reliable and affordable assay method for the routine analysis of methyldopa in bulk and dosage forms